Quality of Dried Anchovy (Stolephorus sp.) from Buru Island Produced by Using Closed Sun Dryer - Imelda Krisanta Enda Savitri; Bernita Silaban; R.B.D. Sormin (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2018)
Anchovies drying method in Saliong, Batuboi village, Kayeli Bay has been done by spreading fish on the ground covered by mat or net due to low cost and easy to apply. However, there are no guarantee in the sanitation and hygienic. The objective of this research was to study the effect of closed sun drying method on the quality of dried anchovies (Stolephorus sp). The method was using closed cabinet sun dryer prototype covered by transparence plastic multi racks. Parameters observed involve: organoleptic, moisture content, acid insoluble, total plate count (TPC), E. coli, Salmonella sp., Vibrio cholera and fungi according to Indonesian national standard reference (SNI). The result showed the dried anchovy have an organoleptic grade refers to appearance, smells and texture were 8.40, 8.33 and 8.27 respectively. Moreover, moisture 17.50%; acid insoluble ash 0.32%; total bacterial (TPC) 6.92x102; E. coli, Salmonella sp., V. cholera and fungi were negative. For comparison, dried anchovy produced by using conventional/traditional drying had an organoleptic grade refers to appearance, smells and texture were 7.67, 7.73 dan 7.87 respectively; while moisture 16.93% ; acid insoluble ash 0.65%; total bacterial (TPC) 1.16 x103; E. coli, Salmonella sp., V. cholera and fungi were negative. According to the SNI 01-2891 BSN 1992, dried anchovy produced by using enclosed sun dryer better than dried anchovy produced by traditional method.